2020
DOI: 10.7759/cureus.9721
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated With Contrast-Induced Nephropathy after Primary Percutaneous Coronary Intervention

Abstract: Background Contrast-induced nephropathy (CIN) after primary percutaneous coronary intervention (PCI) is associated with increased mortality and morbidity. The aim of this study is to determine the frequency of CIN after primary PCI and its association with risk factors in patients with STsegment elevation myocardial infarction (STEMI) at a tertiary care cardiac center in Pakistan. Methodology In this observational study, we included 282 patients who presented with STEMI and underwent primary PCI at the Nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 26 publications
3
9
0
Order By: Relevance
“…These results were comparable to the previous studies. [21,22] Most common risk factor of CIP was contrast volume >150ml 19 (76%) and hypertension found in 17 (68%) cases, followed by diabetes mellitus in 15 (60%) cases, age >65 years in 13 (52%) cases, CHF in 11 (44%) cases, smoking history in 9 (36%) cases and family history of CAD was 4 (16%). Several previous research [23,24] have shown that there is a correlation between an increasing dose of contrast agent used during the surgery and a higher incidence of CIN.…”
Section: Discussionmentioning
confidence: 99%
“…These results were comparable to the previous studies. [21,22] Most common risk factor of CIP was contrast volume >150ml 19 (76%) and hypertension found in 17 (68%) cases, followed by diabetes mellitus in 15 (60%) cases, age >65 years in 13 (52%) cases, CHF in 11 (44%) cases, smoking history in 9 (36%) cases and family history of CAD was 4 (16%). Several previous research [23,24] have shown that there is a correlation between an increasing dose of contrast agent used during the surgery and a higher incidence of CIN.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were divided into two groups: those who received a contrast volume ≥ 200 ml and those who received a contrast volume < 200 ml. The cutoff was set as 200 ml because 100 ml increment of contrast volume is known to be associated with the risk of AKI, and 200 ml is more than the average volume administered at most PCI centers; furthermore, a previous study showed that ≥ 200 ml of contrast volume was the precipitating factor for AKI 2 , 4 , 17 . Angiographical stenosis was defined as > 50% stenosis for left anterior descending artery, left circumflex artery and right coronary artery and ≥ 50% stenosis for left main.…”
Section: Methodsmentioning
confidence: 99%
“…Higher intratubular pressure as a consequence of contrast-induced diuresis, in addition to heightened perivascular hydrostatic pressure, may lead to medullary hypoxia as a result of reduced medullary blood flow in some patients (4). If there is a loss of balance between vasoactive chemicals (such as endothelin and adenosine) and vasodilators (nitric oxide and prostaglandins), renal ischemia may occur (5). A significant amount of urine is required to flush the body of the high osmotic load of the contrast medium.…”
Section: Introductionmentioning
confidence: 99%